Does drug dispensing influence patients’ medication knowledge and medication adherence? A systematic review and meta-analysis - Santana, Elizabete Priscila Costa; Javarini, Haidelucia Rodrigues Vieira; de Araújo, Dyego Carlos Souza Anacleto; Cerqueira-Santos, Sabrina; Reis, Tiago Marques; dos Santos-Junior, Genival Araujo; Rocha, Kérilin Stancine Santos (BMC health services research, 2025)
Inadequate medication knowledge and medication nonadherence by patients are considered an issue in healthcare, as they can lead to negative outcomes, such as therapeutic failures and hospitalization. Even though drug dispensing, which has pharmacist counseling as a core element, is a service traditionally performed by pharmacists, there is still no evidence about the influence of this service on these health outcomes. To evaluate the influence of drug dispensing on patients' medication knowledge and medication adherence. A systematic review was conducted in which a literature search was performed in the PubMed/Medline, Biblioteca Virtual da Saúde, Web of Science, and Embase databases, as well as in gray literature. Two reviewers read the titles, abstracts and complete texts according to the eligibility criteria and extracted the data from the included articles. Original studies-of any design-evaluating the influence of drug dispensing on patients' medication knowledge and/or adherence in community pharmacies were included. The methodological quality was assessed through the tools provided by the JBI Institute. The data was analyzed through qualitative synthesis and a meta-analysis was conducted for randomized controlled trials which used the outcome of medication adherence using the RStudio version 4.3.3 program. A total of 7,590 studies were identified in the initial search, of which 11 articles met the eligibility criteria and were included in this systematic review. The studies were published in Africa, Latin America, Asia, Europe and Australia. Most of the studies were interventional (n = 7). Four studies evaluated the influence of drug dispensing on the patient's medication knowledge, and all showed that knowledge increased after dispensing. Eight studies evaluated the influence of dispensing on medication adherence. Three studies were included in the meta-analysis, which showed moderate heterogeneity (I = 44%, p = 0.17). The results indicated that there was no statistically significant difference in medication adherence post-dispensing (RR: 1.19; 95%CI 0.99 to 1.43, p = 0.07). Six studies met more than 70% of the quality assessment criteria. This systematic review demonstrated that patient's medication knowledge can be increased through drug dispensing. However, the meta-analysis indicated that drug dispensing does not have an impact on medication adherence. Our findings can support evidence-based decisions, guiding the planning and development of public policies and interventions which improve drug dispensing for patients, families, and communities.